KONSEP DIRI DAN MAKNA BAHAGIA DIFABEL KAKI MENURUT PANDANGAN KI AGENG SURYOMENTARAM - , Ryan Sugiarto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Suryometaramâs point of view has strong relationships with self concept, as psychological approach toward Javanese people. Suryomentaran states that rasa (human feeling) is the basic drive for human being, people acts as the embodiment of rasa. Manusia tanpa ciri (a man without attribute) mentioned as the culmination of human achievement. This study aims to investigate self concept of javanese people with foot disability, and describe their ability to reach out and become manusia tanpa ciri (a man without attribute). This study also investigate the meaning of happiness toward javanese people with foot disability, with a set of Suryomentaramâs analysis of kawruh jiwa and the knowledge of happiness. Furthermore, the investigation focuses on two main purposes: (1) understanding self-concept of javanese people with foot disability caused by accident, (2) understanding the meaning of happiness of javanese people with foot disability caused by accident from Ki Ageng Suryomentaramâs (KAS) point of view. This study uses phenomenological approach. Participant were interviewed has characteristics such as: (a) suffering from foot disability caused by accident more than five years, (b) a Javanese, (c) not being treated in rehabilitation yet. The result showed that javanese people with foot disability is able to achieve tatag (spartanâs) level and remain at forth level as âa man without atributeâ. Subject able to step out from the individual attributes when interacting within societies, release from suffering caused by the disability and other attributes. Furthermore, result showed that happiness essentially moves under two conditions in which the first happiness cannot be treated separately from the second one. The first condition of happiness constitutes optimism, pleasure, success, laughter, and wealth, and the second condition of happiness includes happiness for the others such as: social interaction (srawung), mutual sharing, harmony (tentrem), and being a kind man. The meaning of happiness cannot be treated as a separate experience of misery.